The Denial of the Personal, the Preservation of the Status Quo in Teacher Education - Ardra Cole (University of Windsor, 2006)
This paper presents two stories of learning and teaching. Through the stories, the author explores the relationship between personal history-based learning and teaching practice and advocates a process of reflexive inquiry for teacher learning and teacher education. A major focus is on how a curriculum and pedagogy of reflexive inquiry can transform, deepen and broaden conceptions of teacher education as well as make a difference in how teachers see and express themselves in educational contexts. The author also describes the meanings and implications of a personal history pedagogy for teacher education institutions as well as the contextual changes required for such transformative practices to be adopted.